Tooth loss prevalence and risk indicators among adult people visiting community health centers in Nellore district, Andhra Pradesh: A cross-sectional study - S K Shabana Begum; V Chandra Sekhara Reddy; R. V. S. Krishna Kumar; K M Sudhir; G Srinivasulu; S K Noushad Ali (Wolters Kluwer Medknow Publications, 2016)
Introduction: The relationship between oral health and tooth retention is complex. Dental caries and periodontal diseases are the main reasons for tooth loss; the contribution of other modifying factors such as cultural beliefs, socioeconomic characteristics, access to dental care, and dental practitioner's philosophy of treatment may also influence the decision to extract teeth. Aim: The aim of this study is to assess the prevalence and risk indicators of tooth loss in an adult population visiting community health centers (CHCs), Nellore district. Materials and Methods: A cross-sectional study was conducted among adult patients visiting the outpatient wards of 10 CHCs which were selected by multistage random sampling. A total of 450 patients in the age range of 35-74 years were surveyed using a structured questionnaire followed by clinical examination. Questionnaire was regarding age, sex, socioeconomic status (SES), smoking habits, dental visiting patterns, and oral hygiene practices. Clinical examination was performed using dentition status from the WHO pro forma and loss of attachment (LOA) with LOA Index. Results: Overall prevalence of tooth loss was 50.39%. The highest prevalence of tooth loss was reported in 65-74 years old age group (96.18%) and upper lower class. Males had highest tooth loss prevalence (64.29%) with mean tooth loss of 3.08 ± 3.59. Multiple logistic regression done to assess the impact of various independent variables on tooth loss revealed that age, gender, SES, habits of cleaning teeth, frequency of brushing teeth, time of brushing, dietary habits, visit to dentist, dental caries, and LOA had a significant impact on tooth loss. Conclusion: Age, gender, SES, habits of cleaning teeth, frequency of brushing teeth, time of brushing, dietary habits, visit to dentist, dental caries, and LOA were identified as risk indicators for tooth loss among adult people visiting community health centers in Andhra Pradesh.